Cosmology of To Cerekang; The Indigenous Community's Principles of Environmental Conservation - Nurazizah, Nurazizah; Alamsyah, Samsuddin; Dress, Gunther; Hasyim, Baso; Alifah, Alifah; Kartika, Isma (LP2M IAIN Palopo, 2024)
This research aims to understand the cosmological values in the life of the To Cerekang indigenous community. Local wisdom and environmental issues are closely intertwined in the lives of indigenous communities. This research is a descriptive qualitative study with a cosmological study approach. Several stages of data collection such as observation, interviews, and documentation are employed. In the data analysis stage, data reduction, data presentation, and drawing conclusions are conducted. Cosmological values in the conservation efforts of the To Cerekang indigenous community can be seen in various forms such as understanding of the universe, ecosystem interconnectedness, awareness of environmental vulnerability, and commitment to preservation. The To Cerekang indigenous community's understanding of the universe includes the function of ancestral values passed down to subsequent generations. Regarding ecosystem interconnectedness in the To Cerekang indigenous community's life, it is evident in the balanced interaction between humans and their environment. This also relates to the To Cerekang indigenous community's awareness of environmental vulnerability, demonstrated by their collective responsibility to protect various natural resources within their customary areas. This is accompanied by the To Cerekang indigenous community's commitment to environmental preservation, as shown by the commitment of each individual to adhere to all applicable customary rules.